2017
DOI: 10.1186/s12909-017-0930-3
|View full text |Cite
|
Sign up to set email alerts
|

Structured feedback on students’ concept maps: the proverbial path to learning?

Abstract: BackgroundGood conceptual knowledge is an essential requirement for health professions students, in that they are required to apply concepts learned in the classroom to a variety of different contexts. However, the use of traditional methods of assessment limits the educator’s ability to correct students’ conceptual knowledge prior to altering the educational context. Concept mapping (CM) is an educational tool for evaluating conceptual knowledge, but little is known about its use in facilitating the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…The importance of providing feedback on students' maps is emphasised by Morse and Jutras [50] who concluded that 'concept maps without feedback have no significant effect on student performance, whereas concept maps with feedback produced a measurable increase in student problem-solving performance and a decrease in failure rates' (p. 234). Joseph et al [47] have shown that the application of structured feedback (supported by review of lecture notes and dialogue with peers) can help students to increase the sophistication of their maps-particularly moving from simple spoke or chain structures towards more complex net structures [26]. This is consistent with the wider literature on the positive impact of appropriate feedback to improve student learning in Higher Education [51].…”
Section: Rhizomatic Analysis Of Contestations In the Concept Mapping supporting
confidence: 58%
See 2 more Smart Citations
“…The importance of providing feedback on students' maps is emphasised by Morse and Jutras [50] who concluded that 'concept maps without feedback have no significant effect on student performance, whereas concept maps with feedback produced a measurable increase in student problem-solving performance and a decrease in failure rates' (p. 234). Joseph et al [47] have shown that the application of structured feedback (supported by review of lecture notes and dialogue with peers) can help students to increase the sophistication of their maps-particularly moving from simple spoke or chain structures towards more complex net structures [26]. This is consistent with the wider literature on the positive impact of appropriate feedback to improve student learning in Higher Education [51].…”
Section: Rhizomatic Analysis Of Contestations In the Concept Mapping supporting
confidence: 58%
“…Karpicke and Blunt go on to argue that familiarity with a technique (such as concept mapping) is not related to effectiveness, but this seems to be missing the point of the teacher in the classroom and the importance of dialogue and feedback to stimulate higher order thinking. Those who have used concept mapping extensively in their classrooms will know that (whilst the tool can be acquired quickly) mastery of concept mapping and the drawing of high quality maps takes time and practice, supported by feedback and editing of maps to enhance their explanatory power [46,47]. While there were no examples of student concept maps offered by Karpicke and Blunt [40] that would allow the reader to gauge the quality of the data being considered, a subsequent paper by these authors [48] offered an example of a 'retrieval-based concept map'.…”
Section: Rhizomatic Analysis Of Contestations In the Concept Mapping mentioning
confidence: 99%
See 1 more Smart Citation
“…The concepts are represented in a hierarchical structure, with the most general concepts at the top of the map and the more specific concepts arranged hierarchically below [36]. Experimental results show that concept maps are effective and useful for teaching concepts and increasing students' level of factual knowledge in spite of some difficulties [2,30,33,37]. Concept maps are also useful as an assessment tool for facilitating conceptual understanding in different knowledge areas [20,31,51].…”
Section: Of the Online Course-resulting Main Featuresmentioning
confidence: 99%
“…This is obviously the case for the relationship between the wave as a whole and the local oscillations at the different points of a wave propagation medium, and it also applies for the close relationship between the local oscillation energy and the energy propagation in a wave, together with the resulting wave intensity in the case of acoustic waves. Here, the concept map, which is behind the hypertextual index, was most probably a relevant help for building deeper knowledge concerning these interrelationships, according to the considerations in the Rationale section, based on the literature on concept maps (especially ). Figure shows a detail from the hypertextual index with the items that address subtopic 4 as an example of these two subtopics with significant performance rate difference.…”
Section: Students’ Response To the Hypertextual Index Versus The Tradmentioning
confidence: 99%